2005
DOI: 10.1063/1.2000229
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational spectroscopy and dynamics of small anions in ionic liquid solutions

Abstract: Fourier-transform infrared (FTIR) and time-resolved IR spectroscopies have been used to study vibrational band positions, vibrational energy relaxation (VER) rates, and reorientation times of anions in several ionic liquid (IL) solutions. The ILs primarily investigated are based on the 1-butyl-2,3-dimethylimidazolium ([BM(2)IM]) cation with thiocyanate (NCS-), dicyanamide (N(CN)2-), and tetrafluoroborate (BF4-) anions. Spectroscopic studies are carried out near 2000 cm-1 for the C[Triple Bond]N stretching band… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
103
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(129 citation statements)
references
References 63 publications
18
103
4
Order By: Relevance
“…33,34 Experimental studies on the rotational motion of small molecules dissolved in ILs have also been reported. [35][36][37][38][39] We calculated  2 in Eq. 7 by using the measured viscosity data and assuming V of the van der Waals volumes of the cations in Table 3.…”
Section: Cation Molecular Motionmentioning
confidence: 99%
“…33,34 Experimental studies on the rotational motion of small molecules dissolved in ILs have also been reported. [35][36][37][38][39] We calculated  2 in Eq. 7 by using the measured viscosity data and assuming V of the van der Waals volumes of the cations in Table 3.…”
Section: Cation Molecular Motionmentioning
confidence: 99%
“…Much progress has been made in recent years on the measurement and interpretation of their thermodynamic and transport properties. [4,5] The dynamic characteristics of RTILs have also received attention, including studies using optical heterodyne-detected Raman-induced Kerreffect spectroscopy (OHD-RIKES), [6][7][8][9][10] time-resolved infrared, [11] NMR relaxation, [12][13][14][15] and emission [16][17][18] spectroscopies, quasielastic neutron scattering, [20] terahertz spectroscopy, [21][22][23] and dielectric relaxation spectroscopy (DRS). [24][25][26][27][28][29][30][31][32][33][34] Detailed knowledge of the dielectric behaviour of RTILs is particularly important since such properties are critical for understanding their solvation dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…In typical T 1 measurement experiments, the time-dependent absorption change at the peak of the bleach or absorption is probed. 23,[32][33][34][35][36] When the absorption band to be probed is distinctly separate from the other absorption that can be influenced by the IR pump pulse, the decay kinetics at the peak absorption or bleach can be a good representation of the T 1 of the corresponding vibrational mode. The time constants for the decays of the peak absorptions in the transients of Mb heavily overlap with that of the free anion, the decays at the peak absorptions cannot be used to determine their T 1 values.…”
Section: IIImentioning
confidence: 99%